REDEFINISI PIDANA DAN PEMIDANAAN KORPORASI DALAM PERSPEKTIF RANCANGAN UNDANG-UNDANG KITAB UNDANG-UNDANG HUKUM PIDANA - Harkrisnowo, Harkristuti (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2019)
Corporations as subjects of criminal law has been in existence in Indonesia since 1955 with the enactment of the Emergency Law no. 7. However, apparently efforts to catch corporations into the net of criminal law is definitely unsatisfactory, for despite the many forms and faces of corporate crimes, the past six decades witnessess a negligible number of corporations being brought to justice. But obviously this is not only a problem in Indonesia, but also in other countries, despite the fact that most countries do have laws and regulations regarding corporate criminal liability. The skepticism againts the enforcement of the law towards corporations eventually creates the perception of corporate impunity. What factors are correlated with this condition, are we in the right track of formulating the term corporation and are there potential criteria for corporate criminal liability, and what criminal sanctions are most appropriate for corporation will be discussed in this paper.